1993
DOI: 10.1080/00207149308414539
|View full text |Cite
|
Sign up to set email alerts
|

Response Expectancy as a Mediator of Hypnotizability Modification: A Brief Communication

Abstract: The role of response expectancy in bringing about increases in hypnotic susceptibility by use of the Carleton Skill Training Program (CSTP) was assessed with 27 subjects selected for their low hypnotizability scores. Subjects were randomly assigned to one of two conditions: 13 received the CSTP to increase their hypnotic susceptibility, and 14 received no training. In addition to assessing hypnotizability, hypnotic response expectancies were assessed before and after training. With pretreatment hypnotizability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…(see for e.g. Kirsch, 1985;Gearan and Kirsch, 1993). 13 It is difficult to clearly differentiate concomitants to hypnosis per se, since most of the experiments done in the field have used various suggestions in addition to a hypnotic induction.…”
Section: Notesmentioning
confidence: 99%
“…(see for e.g. Kirsch, 1985;Gearan and Kirsch, 1993). 13 It is difficult to clearly differentiate concomitants to hypnosis per se, since most of the experiments done in the field have used various suggestions in addition to a hypnotic induction.…”
Section: Notesmentioning
confidence: 99%
“…However, Spanos and his colleagues have also contended that some of the variance in responsiveness is due to differences in knowing how to respond (Gorassini & Spanos, 1986). This has not been my position (see Gearan & Kirsch, 1993), but in fairness, it should be noted that Spanos bolstered his hypothesis with considerable data (reviewed in Gorassini & Spanos, 1999) showing that when taught strategies for responding, many low suggestible subjects become highly suggestible. Thus, Spiegel's claim that "the evidence is clearly against this position" is simply wrong.…”
Section: Hypnotic Suggestibility As a Traitmentioning
confidence: 80%
“…This suggests that expectation-induced mechanisms, which are more effective in highs than in lows , are associated with those sustaining the conditioned analgesia. However, in highs the expectation of pain relief does not totally account for the suggestion induced analgesia (Gearan and Kirsch, 1993 ) and it is unlikely that the expectation of analgesia could be sustained by opioid mechanisms, in contrast to the general population (Amanzio and Benedetti, 1999 ; Benedetti et al, 1999 ; Petrovic et al, 2002 ; Zubieta et al, 2005 ; Scott et al, 2008 ; Babel et al, 2017 ). In fact, not only the effects of suggestions is not abolished by naloxone (Moret et al, 1991 ) but, in addition, highs display the μ1 polymorphism (Presciuttini et al, 2018 ) which has been found associated with low sensitivity to opiates, low placebo response (Trescot and Faynboym, 2014 ; Bartošová et al, 2015 ; Peciña and Zubieta, 2015 ) and larger opiates consumption for post-surgery (Zhang et al, 2005 ; Boswell et al, 2013 ; Sia et al, 2013 ; Ren et al, 2015 ) and cancer pain (Gong et al, 2013 ; Wan et al, 2015 ; Yao et al, 2015 ).…”
Section: Hypnotizability and Expectation Of Pain Reliefmentioning
confidence: 99%